Jihad Harta dan Kesejahteraan Ekonomi Pada Keluarga Jamaah Tabligh: Perspektif Teori Tindakan Sosial Max Weber - Khusniati Rofi'ah; Moh Munir (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2019)
This article aims to assess the phenomenon of wealth jihad and family economic well-being among the Tablighi Jamaah group in Sidoharjo Ponorogo Village, associated with Max Weber's theory of social action, thus providing a holistic meaning of the meaning of wealth jihad and economic welfare. Using qualitative methods, and participatory approaches, this study produced several findings: First, wealth jihad according to members of the Tablighi Jamaat is an important and important thing. Second, the meaning of economic welfare according to members of the Tablighi Jamaah is when a person can live peacefully with his family even with simple needs. Third, the implication of the existence of wealth jihad against the economic welfare of the family of the Tabligh Jama'at is that they must issue assets to fight in the way of Allah, but they do not feel deficient. In the perspective of Max Weber's action theory, the actions of wealth jihad and economic well-being carried out by the Jamaah Tabligh group can be categorized as goal-oriented actions (Rational Instrumentally), Value-oriented actions, Affective / especially emotional actions and traditional action.Artikel ini bertujuan mengkaji fenomena jihad harta dan kesejahteraan ekonomi keluarga dikalangan kelompok Jamaah Tabligh di Desa Sidoharjo Ponorogo dikaitkan dengan teori tindakan sosial Max Weber, sehingga memberikan pemaknaan yang holistik tentang makna jihad harta dan kesejahteraan ekonomi. Dengan menggunakan metode kualitatif, dan pendekatan partisipatif, kajian ini menghasilkan beberapa temuan: Pertama, jihad harta menurut anggota Jamaah Tabligh merupakan suatu hal yang penting dan utama. Kedua, makna kesejahteraan ekonomi menurut anggota Jamaah Tabligh adalah ketika seseorang dapat hidup dengan damai bersama keluarga meskipun dengan kebutuhan yang sederhana. Ketiga, implikasi dari adanya jihad harta terhadap kesejahteraan ekonomi keluarga Jamaah Tabligh adalah mereka harus mengeluarkan harta untuk berjuang di jalan Allah, akan tetapi mereka tidak merasa kekurangan. Dalam perspektif teori tindakan Max Weber, maka tindakan jihad harta dan kesejahteraan ekonomi yang dilakukan oleh kelompok Jamaah Tabligh ini dapat dikategorikan sebagai tindakan yang berorientasi tujuan (Instrumentally Rasional), tindakan berorientasi nilai (Value Rational), Tindakan afektif (affectual/especially emotional) dan tindakan tradisional.